Zic2 regulates the kinetics of neurulation - Nagai, Takeharu (The National Academy of Sciences, 2000)
Mutation in human ZIC2, a zinc finger protein homologous to Drosophila odd-paired, causes holoprosencephaly (HPE), which is a common, severe malformation of the brain in humans. However, the pathogenesis is largely unknown. Here we show that reduced expression (knockdown) of mouse Zic2 causes neurulation delay, resulting in HPE and spina bifida. Differentiation of the most dorsal neural plate, which gives rise to both roof plate and neural crest cells, also was delayed as indicated by the expression lag of a roof plate marker, Wnt3a. In addition the development of neural crest derivatives such as dorsal root ganglion was impaired. These results suggest that the Zic2 expression level is crucial for the timing of neurulation. Because the Zic2 knockdown mouse is the first mutant with HPE and spina bifida to survive to the perinatal period, the mouse will promote analyses of not only the neurulation but also the pathogenesis of human HPE.